2003
DOI: 10.1021/ja035191v
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electron-Transfer Processes in Reactions of Diarylcarbenium Ions and Related Quinone Methides with Nucleophiles

Abstract: Second-harmonic alternating current voltammetry has been used to determine one-electron reduction potentials of 15 diarylcarbenium ions and 5 structurally analogous quinone methides, which have been employed as reference electrophiles for the development of nucleophilicity scales. A linear correlation (r(2) = 0.993) between the empirical electrophilicity parameters E and the reduction potentials in acetonitrile (E = 14.091E degrees (red) - 0.279) covering a range of 1.64 V (or 158 kJ mol(-)(1)) has been observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…The electrophilicity of a number of noncharged activated olefins consisting of the three arylidenemalonitriles 11 a – c and of various quinone methides (see Figure 5) have been determined 13f. 26, 27 As revealed by Figure 5, the reactivity of all these compounds is considerably lower than that of NBDF. With an E value of −9.42, the most reactive arylidenemalonitrile studied, namely 11 a , is by more than three orders of magnitude less electrophilic than NBDF.…”
Section: Resultsmentioning
confidence: 99%
“…The electrophilicity of a number of noncharged activated olefins consisting of the three arylidenemalonitriles 11 a – c and of various quinone methides (see Figure 5) have been determined 13f. 26, 27 As revealed by Figure 5, the reactivity of all these compounds is considerably lower than that of NBDF. With an E value of −9.42, the most reactive arylidenemalonitrile studied, namely 11 a , is by more than three orders of magnitude less electrophilic than NBDF.…”
Section: Resultsmentioning
confidence: 99%
“…[17b] Recently, we have examined combination reactions of our reference electrophiles 2 with a large variety of nucleophiles, and have found that outer-sphere electron transfer processes do not occur in any of the reactions so far investigated. [18] To examine whether electron transfer takes place in the reactions examined in this work, the actually observed activation free energies, ∆G ‡ obsd. , were compared with the free energies of electron transfer, ∆G°E T .…”
Section: Resultsmentioning
confidence: 99%
“…[18] To examine whether electron transfer takes place in the reactions examined in this work, the actually observed activation free energies, ∆G ‡ obsd. , were compared with the free energies of electron transfer, ∆G°E T .…”
mentioning
confidence: 99%
“…Ofial et al [62] have demonstrated that the oxidation potentials of benzhydryl radicals and hence the driving force DG ET for electron transfer depend on the aryl substituents, but experimental data for the m-fluoro compounds are not available.…”
Section: Influence Of Substitution and Solvent Polarity On The Intermmentioning
confidence: 99%